Correlation of Sodium and Serum Albumin Levels with the Severity of Acute Ischemic Stroke - Ullifannuri Rachmi; Rima Yuliati Muin; Suci Aprianti; Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Management of acute ischemic stroke patients based on their severity in emergency services is critical. One of the easy, fast, and affordable biochemical markers is serum sodium and albumin, which correlate with the severity of acute ischemic stroke. This research aimed to analyze the correlation of serum sodium and albumin levels with the severity of acute ischemic stroke. This retrospective study used medical record data of 165 acute ischemic stroke patients for the period January 2018-April 2021 at Dr. Wahidin Sudirohusodo Hospital, Makassar. Patients were classified according to the degree of mild, moderate, or severe stroke through the NIHSS score. Examination of serum sodium was done by Electrolyte Analyzer NOVA 5 and albumin with ABX Pentra 400. Data normality test Kolmogorov-Smirnov. The statistical test used the Kruskal-Wallis, Mann-Whitney, and Spearman (significant if p<0.05). There was a negative correlation between serum albumin levels and the severity of stroke patients (p<0.001; r= -0.327). There was no significant association between serum sodium and ischemic stroke severity. There was a statistically significant difference in serum albumin levels in patients with mild and moderate stroke (p=0.001), mild and severe (p=0.001). Albumin correlates the outcome of acute ischemic stroke patients (p<0.001), cut-off ≤ 3.25 g/dL (sensitivity 66.7%, specificity 50%). Hypoalbuminemia exacerbates cytotoxic edema by causing water and ions to cross the blood-brain barrier to the astrocytes resulting in further neuron damage. Albumin has a correlation with the NIHSS score (p<0.001; r= -0.327). The lower the albumin level, the higher the NIHSS score, indicating the ischemic stroke severity.